Awareness and Attitude about Social, Ethical and Legal issues Related to Assisted Reproductive Techniques (A.R.T) amongst Medical Students and Interns in a Tertiary Care Hospital at Chennai - P Shruthi; Sri Jayanth (Institute of Medico-legal Publications Pvt Ltd, 2021)
Infertility is an issue on the rise worldwide. Infertility treatment globally has undergone a gradual revolutionfrom the traditional treatment to the use of assisted reproductive technology (ART). ART is presently themost sought after technology that successfully treats millions of infertile couples over the world. However,the utilization of ART still differs between various nations owing to varying socioeconomic, cultural andreligious reasons. The sudden increase of this technology has introduced numerous social, ethical, and legalchallenges. This paper assesses the awareness level and attitude amongst medical students and interns inChennai regarding some of the most vital and tricky topics in the field of ART and outlines the ethical,legal and social challenges they bring in. This questionnaire-based study involved 427 participants whoencompassed medical students and interns from tertiary care hospital at Chennai. The responses werecollected, tabulated and statistically analysed. About 2/3rd of the participants were females. 94% of therespondents declared that they are aware of ART (401), 63% answered that all the information was obtainedfrom the medical college. Over 2/3rd of the study population was aware of one of the ART methods. 70.8%(302) amongst the participants felt that ART solved all problems of infertility.86.7% of the respondents(370) knew that Spousal agreement to opt for A.R.T is a must. 90.6% (387) of the study population were ofthe opinion that revealing the identity of the sperm donor would cause psychological, social and attitudinalissues among the recipients & the spouse. 29.6% of the participants felt that donation of the surplus embryosfor research purposes was the best option. The gaps in knowledge about newer methods and proceduresregarding ART were identified. Medical students must be agents of socio-medical information and thismakes them good ambassadors for healthy living and fertility awareness. The introduction of governmentrun ART centres and reduction in the cost of the services will go a long way in encouraging more personsto use the services.